Duración del tratamiento que se brinda en el Hospital Diurno a adultos con esquizofrenia y su relación con las habilidades psicosociales - Román Zárate, Verónica (2014)
The aim of this paper is to present the results of secondary research about the time required to provide treatment in a day hospital for adults with schizophrenia, in order to develop psychosocial skills. The Day Hospital of the National Psychiatric Hospital currently receives people in both acute and chronic, and people with a chronic condition have five or more years of participating in the programs offered at that hospital; although some havealready reached the goals set at the time of admission, have not been discharged of the hospital, a situation that significantly limits the admission of more people who need this care alternative specializing in mental health and psychiatry for the development of psychosocial skills. . Against this background, the researchers make a question in PICO format (patient , intervention, comparison, outcomes), Later, information was sought on various databases suggested in the course “Clinical Practice Evidence-Based” taught by the Program for Collaborative Research-Based Nursing Evidence of Costa Rica (CIEBE-CR). 37 documents related to the issue was detected of which just five met quality criteria. These were analyzed by applying the criteria set out in Critical Appraisal Skills Programme Spanish (CASPe) to answer the clinical question. The researchers conclude that there is insufficient evidence to determine the time it takes a person with schizophrenia in a day hospital to developpsychosocial skills and be discharged, so it is important to perform primary research, leading to the decisionmaking regarding theme.